1964
DOI: 10.1113/jphysiol.1964.sp007376
|View full text |Cite
|
Sign up to set email alerts
|

The activation of sexual behaviour in cats by the subcutaneous administration of oestrogen

Abstract: The female cat possesses a characteristic and highly stereotyped pattern of sexual behaviour, which is remarkably constant in individual animals (Stricht, 1911; Greulich, 1934;Bard, 1939;Dawson, 1950;Michael, 1958). The pattern of oestrous behaviour depends upon the secretory activity of the ovaries and is never observed in immature, anoestrous or ovariectomized animals (Bard, 1939;Michael, 1961). It can therefore be regarded as a pattern of behaviour that is hormone-dependent. This study deals mainly with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

1964
1964
1986
1986

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…The latent period to mating was found to be 5-6 days in all four animals (see Michael & Scott, 1964). These animals were therefore shown to have a similar order of sensitivity to systemic oestrogen.…”
Section: Hypothalamus and Sexual Behaviourmentioning
confidence: 75%
See 4 more Smart Citations
“…The latent period to mating was found to be 5-6 days in all four animals (see Michael & Scott, 1964). These animals were therefore shown to have a similar order of sensitivity to systemic oestrogen.…”
Section: Hypothalamus and Sexual Behaviourmentioning
confidence: 75%
“…Most animals in this group had small implants (< 0-2 mg). Since it has been shown that prolonged, daily systemic administration of small doses of stilboestrol ester and oestradiol results in full development of the genital tracts in ovariectomized cats, without producing mating (Michael & Scott, 1964), it is improbable that the response seen in this group of animals (sustained mating without genital-tract development) is due to an effect exerted by absorption of the stilboestrol ester into the general systemic circulation. It is therefore likely that the ester implants were acting by a local and direct effect on the surrounding neural tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations